Sistem Informasi Pengelolaan Barang Inventaris Berbasis Web di Perumda BPR Bank Cirebon - Dini Maryani; Nana Suarna (Pusat Riset dan Inovasi Nasional, 2023)
The limitations of recording inventory of goods at Perumda BPR Bank Cirebon are still manual. This causes a relatively long inventory reporting time and the possibility of data errors. For this reason, an inventory web application can help manage inventory inventory at Perumda Bank Cirebon. Designing a web-based inventory information system is the purpose of this research at Perumda BPR Bank Cirebon. The method used includes going through the stages of analysis, design, execution, interviews, and observation. By using the PHP programming language and MySql database, this information system was created. The finding of this study is an inventory management information system that can facilitate agencies and companies in recording company inventories and minimizing the possibility of data errors